2021
DOI: 10.1002/ajb2.1749
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of divergence: the selfing syndrome in Ipomoea lacunosa

Abstract: Highly selfing plant species frequently display a distinctive suite of traits termed the selfing syndrome. Here we tested the hypothesis that these traits are grouped into correlated evolutionary modules and determined the degree of independence between such modules. Methods: We evaluated phenotypic correlations and QTL overlaps in F2 offspring of a cross between the morning glories Ipomoea lacunosa and I. cordatotriloba and investigated how traits clustered into modules at both the phenotypic and genetic leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…As pointed out by Cutter (2019), deciphering the relative contribution of adaptive changes vs relaxed selection for any trait individually remains challenging and few studies have attempted it. In morning glory (Ipomoea lacunosa), Rifkin et al (2021) used Q ST -F ST comparisons to identify selection associated to the divergence between selfers and outcrossers on traits ranging from corolla size to early growth. Divergence between selfers and outcrossers was found to be under selection for corolla size and nectar traits, but not for early growth or pollen traits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out by Cutter (2019), deciphering the relative contribution of adaptive changes vs relaxed selection for any trait individually remains challenging and few studies have attempted it. In morning glory (Ipomoea lacunosa), Rifkin et al (2021) used Q ST -F ST comparisons to identify selection associated to the divergence between selfers and outcrossers on traits ranging from corolla size to early growth. Divergence between selfers and outcrossers was found to be under selection for corolla size and nectar traits, but not for early growth or pollen traits.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is not explained by some ubiquitous genes given the small overlap that we found between the three tissues. One central question is whether selfing syndrome trait evolution arises from relaxed selection (random genetic drift), from adaptive re-allocation of resources or from a mixture of both (Cutter, 2019;Rifkin et al, 2021;Tsuchimatsu & Fujii, 2022). As pointed out by Cutter (2019), deciphering the relative contribution of adaptive changes vs relaxed selection for any trait individually remains challenging and few studies have attempted it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pleiotropy and modularity may have played a critical role in the evolutionary diversification of organismal forms in general [ 21 , 22 , 24 ] and flower form and function in particular [ 9 , 44 ], because selection on one trait will result in correlated changes in functionally related traits. Indeed, floral traits associated with pollinator shifts have been subjected to quantitative trait locus (QTL) analysis in a wide range of sympetalous taxa, including Mimulus [ 11 , 46 ], Leptosiphon [ 47 ] , Ipomopsis [ 48 ], Penstemon [ 18 ], Petunia [ 49 ], and Ipomoea [ 50 ]. These studies showed that corolla tube, stamen, and style lengths are not only genetically correlated but also frequently co-localized to the same QTL, consistent with a role of pleiotropic QTLs underlying intra-floral integration and in facilitating rapid floral form diversification.…”
Section: Discussionmentioning
confidence: 99%